Mapping the Factors Influencing Success of Massive Open Online Courses (MOOC) in Higher Education - Albelbisi, Nour; Yusop, Farrah Dina; Salleh, Umi Kalsum Mohd (Modestum, 2018)
Massive Open Online Courses (MOOC) is a new phenomenon in online learning that has aroused increasing interest by researchers as a significant contribution to improving educational system quality and openness. The purpose of this paper is to compile and analyze MOOC research that has been published between 2012 and 2016. A systematic analysis technique was employed and Template Analysis (TA) approach was used for mapping MOOC research into three dimensions in accordance with the Biggs 3P model. First dimension is Presage, include the following factors: Learners' characteristics with sub-factors (learner demographics, learner motivation, and interactivity) and instructor. Second, Process, including factors of pedagogy, pattern of engagement, instructional design, assessment, credit, plagiarism, sustainability, and learning analytics. Third dimension is Product, including factors of student dropout rate and MOOC quality. This classification is aimed at providing a comprehensive overview for readers interested in MOOCs who seek to understand the critical success factors influencing MOOC success.